2007
DOI: 10.1016/s1028-4559(07)60008-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunohistochemical and Fluorescence In Situ Hybridization Assessment for HER-2/neu Status in Taiwanese Breast Cancer Patients

Abstract: The current algorithm to use HER-2 FISH as a supplementary role to IHC HercepTest 2+ may need some modifications according to the local setting. TOP2A FISH adds little value to HER-2 FISH and IHC staining in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…Gene amplification could be demonstrated only in some of the samples that are found 2+ by IHC (Yeh). Studies have reported that FISH positivity in IHC 2+ samples varies between 7% and 89% (Ciampa et al, 2006;Rossi et al, 2006;Kuo et al, 2007;Sui et al, 2009;Goud et al, 2012;Zhang et al, 2012). Such diverse results might be due to the differences in the number of patients included in studies, centers' and/or pathologists' experience, and the test kits used.…”
Section: Discussionmentioning
confidence: 99%
“…Gene amplification could be demonstrated only in some of the samples that are found 2+ by IHC (Yeh). Studies have reported that FISH positivity in IHC 2+ samples varies between 7% and 89% (Ciampa et al, 2006;Rossi et al, 2006;Kuo et al, 2007;Sui et al, 2009;Goud et al, 2012;Zhang et al, 2012). Such diverse results might be due to the differences in the number of patients included in studies, centers' and/or pathologists' experience, and the test kits used.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have confirmed a high concordance rate in breast carcinomas with IHC score 3? or 1?/0 between these two techniques [6,7]. However, discrepancies in the published literature regarding the equivocal cases (IHC 2?)…”
Section: Discussionmentioning
confidence: 99%
“…or 1? cases [6,7]. However, variable findings with a high rate of falsepositive results were observed by follow-up negative FISH in equivocal IHC 2?…”
Section: Introductionmentioning
confidence: 99%
“…Countries with the same level of resources as Iran, such as Saudi Arabia, Egypt and Taiwan, have shown the same variations in the HER-2-positive breast cancer rate (El-A Helal et al, 2000;Kuo et al, 2007;Arafah., 2012). Taken together, we maintain that standardization is the first step toward improvement in IHC diagnosis by the HER-2 biomarker in breast cancer in Iran.…”
Section: Discussionmentioning
confidence: 99%